Strategy Followed Structure: Management Consulting and the Creation of a Market for “Strategy,” 1950–2000 - McKenna, Christopher (History and Strategy, 2012)
Purpose – This chapter traces the creation of a market for strategy by management consulting firms during the second half of the twentieth century in order to demonstrate their impact in shaping debates in the subject and demand for their services by corporate executives.Design/methodology/approach – Using historical analysis, the chapter draws on institutional theory, including institutional isomorphism. It uses both primary and secondary data from the leading consulting firms to describe how consultants shifted from offering advice on organizational structure to corporate strategy and eventually to corporate legitimacy as a result of the changing economic and regulatory environment of the time.Findings/originality/value – This study provides a historical context for the emergence of corporate and competitive strategy as an institutional practice in both the United States and around the world, and provides insights into how important this history can be in understanding the debates among consultants and academics during strategy's emergence as an academic subject and practical application.